The roles of X rays and other types of electromagnetic radiation in evaluating paintings for forgery and restoration. (June 2016) - Moran, Thea C.; Kaye, Alan D.; Rao, Aravinda; Bueno, Franklin Rivera
Abstract: Radiologists are experts in the use of electromagnetic radiation (EMR) to diagnose, and sometimes treat, disease. Medicine, however, is not the only industry which uses EMR to problem solve. EMR has a long standing role in the forensic examination of cultural properties. This article examines the roles of xrays and, to a lesser degree, gamma rays and beta particles in ruling out forgery and guiding the restoration of paintings. Of the 3 aforementioned EMR types, xrays have the largest role in painting authentication and restoration; much of this article is an overview of the different mechanisms by which xrays can be generated, as well as the information gleaned, from the different technologies in the forensic examination of paintings. Currently, the best method which uses EMR to examine paintings in 2 or 3D is optical coherence tomography (OCT). While OCT is not a widely known modality to the radiologist, it is a known technique in ophthalmology. The physics of OCT and the information yielded during painting examination will be discussed. While there is a high demand for forensic art experts, there are obstacles a radiologist would face should he/she decide to expand, or divert, their practice into this fascinating field. Highlights: Low energy beams, stratigraphy, stereopairs and postprocessing are useful in XRR. XRF and PIXE, each with pros and cons, use xrays to determine elemental composition. NA determines composition via gamma rays and creates images via beta particles. OCT uses low intensity light and interferometry to analyze painting layers in 2/3D. Threat of litigation is a large obstacles to diverting into this kind of career.